2004
DOI: 10.1017/s0266462304001230
|View full text |Cite
|
Sign up to set email alerts
|

Readmission rate as an indicator of hospital performance: The case of Spain

Abstract: Most readmissions in our hospital were unavoidable. Thus, readmission rate might not be considered a valid indicator of quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
0
31
0
2
Order By: Relevance
“…Some studies found that most readmissions were unavoidable and conclude that readmission rates should not be used as a valid indicator of QOC 7,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that most readmissions were unavoidable and conclude that readmission rates should not be used as a valid indicator of QOC 7,18 .…”
Section: Discussionmentioning
confidence: 99%
“…A researcher and an experienced physician concurrently used a set of criteria derived from previously published research (Table 1) [7], in order to assign the readmission into one of the two categories. An agreement was reached by a discussion between the two professionals in the case of discordant opinions.…”
Section: Methodsmentioning
confidence: 99%
“…Clarke 10 Gautam 14 Halfon 23 Kirk 31 Shalchi 38 Williams 9 Ruiz 34 Oddone 16 Phelan 37 Halfon 30 Kelly 13 Kwok 19 MacDowell 7 Maurer 29 Vinson 11 Graham 5 Haines-Wood 15 Jimenez-Puente 28 McInness 8 Stanley 35 Madigan 22 Balla 32 Courtney 26 Frankl 12 Levy 21 McKay 17 Miles 20 Munshi 24 Popplewell 6 Sutton 25 Witherington 36 Experton 18 Friedman 27 Goldfield (Table 4). Error bars = 95% confidence intervals.…”
Section: % Readmissions Deemed Avoidablementioning
confidence: 99%